Underwater noise from airplanes: An overlooked source of ocean noise. (December 2018) - Erbe, Christine; Williams, Rob; Parsons, Miles; Parsons, Sylvia K.; Hendrawan, I Gede; Dewantama, I. Made Iwan
Abstract: The effects of underwater noise pollution on marine life are of increasing concern. Research and management have focussed on the strongest underwater sound sources. Aerial sound sources have understandably been ignored as sound transmits poorly across the air-water interface. However, there might be situations when air-borne noise cannot be dismissed. Commercial passenger airplanes were recorded in a coastal underwater soundscape exhibiting broadband received levels of 84–132 dB re 1 μPa rms. Power spectral density levels of airplane noise underwater exceeded ambient levels between 12 Hz and 2 or 10 kHz (depending on site) by up to 36 dB. Underwater noise from airplanes is expected to be audible to a variety of marine fauna, including seals, manatees, and dolphins. With many of the world's airports lying close to the coast, it is cautioned that airplane noise not be ignored, in particular in the case of at-risk species in small, confined habitats. Highlights: Major airports around the globe exist on the water edge. Underwater noise from airplanes was detectable at 12 Hz–10 kHz. It exceeded ambient levels by up to 36 dB (received levels 84–132 dB re 1 μPa). While underwater noise from individual planes was low, overflights may be frequent. Impacts may be non-negligible for at-risk species in confined habitats.